Land cover classification from multispectral data using computational intelligence tools - Mora, André (2017)
This work was partially funded by FCT Strategic Program UID/EEA/00066/203 of the Center of Technologies and System (CTS) of UNINOVA-Institute for the Development of new Technologies. It is also partially based on work from COST Action TD1403 "Big Data Era in Sky and Earth Observation", supported by COST (European Cooperation in Science and Technology).